2019
DOI: 10.1002/hep.30693
|View full text |Cite
|
Sign up to set email alerts
|

NOD‐like receptor C4 Inflammasome Regulates the Growth of Colon Cancer Liver Metastasis in NAFLD

Abstract: Nonalcoholic fatty liver disease (NAFLD) enhances the growth and recurrence of colorectal cancer (CRC) liver metastasis. With the rising prevalence of NAFLD, a better understanding of the molecular mechanism underlying NAFLD‐associated liver metastasis is crucial. Tumor‐associated macrophages (TAMs) constitute a large portion of the tumor microenvironment that promotes tumor growth. NOD‐like receptor C4 (NLRC4), a component of an inflammasome complex, plays a role in macrophage activation and interleukin (IL)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 46 publications
(88 reference statements)
0
35
1
Order By: Relevance
“…Some animal research also presented a different conclusion. The murine models revealed that hepatic steatosis induced by a high-fat diet increased the metastatic tumor burden of colon cancer tumors metastatic to the liver, and the changes in the liver microenvironment caused by fatty liver established a more sensitive microenvironment for metastasis when compared with normal liver (38)(39)(40). However, the opposite conclusion was discovered in a rat model (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some animal research also presented a different conclusion. The murine models revealed that hepatic steatosis induced by a high-fat diet increased the metastatic tumor burden of colon cancer tumors metastatic to the liver, and the changes in the liver microenvironment caused by fatty liver established a more sensitive microenvironment for metastasis when compared with normal liver (38)(39)(40). However, the opposite conclusion was discovered in a rat model (41).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, this study explored the role of NLRC4 and interleukin (IL)-1β in the growth of metastatic liver tumors under NAFLD-related liver microenvironment, emphasizing the effect of inflammation changes in NAFLD on the metastatic microenvironment. The study concluded that in NAFLD, NLRC4 contributes to M2 TAMs polarization, IL-1β and vascular endothelial growth factor (VEGF) production in TAMs, which promotes the growth of metastatic liver tumors in CRC (40).…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ cancer tumorigenesis and participates in anti-apoptotic pathways downstream of p53 75 . In addition, a recent study showed that NLRC4 mediates M2 TAM infiltration and angiogenesis through VEGF production in metastatic colon cancer 76 .…”
Section: Characterization Of Genes and Pathways Involved In Patients'mentioning
confidence: 99%
“…Recent reports have also implicated NLRC4 in tumor progression. NLRC4 and Caspase-1 were found to promote the metastasis of breast and colon cancer in obese mice, but not those fed on normal-fat diets (Kolb et al, 2016;Ohashi et al, 2019). In contrast, NLRC4 and Caspase-1 were reported to protect mice from chemically-induced colon cancer (AOM/DSS) (Hu et al, 2010), although another report found that Caspase-1 but not NLRC4 was protective in the same model (Allen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%